Gestión administrativa y su efecto en el buen vivir de los adultos mayores en el ministerio de inclusión económica Y social del cantón Quevedo, año 2022 - Vera Molina, Mariuxi Magaly (2023)
This research project aims to analyze the administrative management of the Ministry of Economic and Social Inclusion in the Quevedo canton during the year 2022. The objective is to analyze how administrative practices impact the quality of life of the demographic population in question. In the theoretical framework, fundamental topics are addressed based on the conceptualization, theory and legal regulations relevant to the research. To carry out the project, analytical, deductive and descriptive methods are used. A visit is made to the organization to obtain an overview of how situations are handled in its environment. The methodology includes the use of analytical, inductive and deductive methods. We work with a total population of 131 older adults who receive benefits from a gerontological center. Information is collected through interviews and censuses, and analyzed using technological skills. The results reveal that administrative management highlights aspects such as the allocation of resources, accessibility to social programs, the quality of medical care and the promotion of activities to contribute to the comprehensive well-being of older adults. Through this analysis, the strengths and weaknesses in the administrative management of the Ministry are identified, with the purpose of proposing specific improvements that optimize the positive impact on the lives of older adults in the Quevedo canton. In conclusion, the actions of the administrative management of the MIES are currently focused on improving the good life of older adults. This reflects a significant commitment to a proactive approach, and the implementation of social projects demonstrates a willingness to address various issues, from poverty to vulnerability.